The economic consequences of AIDS mortality in South Africa - Ardington, Cally; Bärnighausen, Till; Case, Anne; Menendez, Alicia (Journal of development economics, 2014)
We quantify the impact of adult deaths on household economic wellbeing, using a large longitudinal dataset spanning more than a decade. Verbal autopsies allow us to distinguish AIDS mortality from that due to other causes. The timing of the lower socioeconomic status observed for households with AIDS deaths suggests that the socioeconomic gradient in AIDS mortality is being driven primarily by poor households being at higher risk for AIDS, rather than AIDS impoverishing the households. Following a death, households that experienced an AIDS death are observed being poorer still. However, the additional socioeconomic loss following an AIDS death is very similar to the loss observed from sudden death. Funeral expenses can explain some of the impoverishing effects of death in the household. In contrast, the loss of an employed member cannot. To date, antiretroviral therapy has not changed the socioeconomic status gradient observed in AIDS deaths.
Gesehen am 09.03.2018